KESEJAHTERAAN LANJUT USIA DAN BEBERAPA FAKTOR PENENTUNYA DI KECAMATAN DENPASAR SELATAN - Arissuhandana, I Wayan Yogi; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 6 (2022): VOL 11 NO 6, JUNI 2022 [2045-2480]DO - 10.24843/EEP.2022.v11.i06.p07, 2022)
The elderly population generally begins to experience a decline in both physical and psychological health, but they still hope for a better life welfare possibility. The objectives to be achieved in this research are : 1) To analyze the effect of family social support, health, work status and education level simultaneously on the welfare of the elderly in South Denpasar District. 2) To analyze the effect of family social support, health, work status and education level partially on the welfare of the elderly in South Denpasar District. 3) To find out how high the level of elderly welfare in South Denpasar District. The population in this study were residents aged 60 years and over who live in South Denpasar District and the sample used the Slovin formula as many as 100 elderly people. This research uses nonrandom sampling technique, which then the sample is taken by accidental sampling. The analysis technique used is multiple linear regression analysis. The results of the study found that the welfare level of the elderly population in South Denpasar District was classified as very high. Simultaneously, family social support, health access, work status and education level affect the welfare of the elderly population in South Denpasar District. Partially family social support, health access, work status and education level have a positive and significant effect on the welfare of the elderly population in South Denpasar District.   Keywords: Elderly welfare, family social support, health access, work status and education level